Potential of the stock trade of Bangladesh: An overview of BRAC EPL stock brokerage - Binte Zahid, Jannat (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.